Implementasi Kewajiban Tanggung Jawab Sosial Perseroan Terbatas Bidang Sumber Daya Alam di Kabupaten Kutai Barat - Sopian, Agus; Indrayanti, Kadek Wiwik (Postgraduate University of Merdeka Malang, 2024)
The legal product in the form of a Regent's Regulation issued by the West Kutai Regency Government which specifically regulates Guidelines for the Implementation of Corporate Social Responsibility is a form of control function over companies operating in the West Kutai Regency area by the West Kutai Regency Government. Based on the description above, this article examines and analyzes the Implementation of the Social Responsibility Obligations of Limited Liability Companies in the Natural Resources Sector Law Number 40 of 2007 concerning Limited Liability Companies in West Kutai Regency and the factors that hinder its implementation. The research method used in this research is an empirical legal research method. Trubaindo Coal Mining in implementing the Regulations on Limited Liability Company Social Responsibility Obligations in the field of natural resources based on Law Number 40 of 2007 concerning Limited Liability Companies in West Kutai Regency has implemented the company's corporate social responsibility in accordance with the program required by the people of Muara Begai Village. Meanwhile, the inhibiting factors that arise in implementing implementation are not being able to differentiate between needs and desires, there are several groups that prioritize personal interests rather than the people at large, of course this will interfere with the company in grouping the right groups that require Corporate Social Responsibility. The lack of Human Resources (HR) cannot be denied as an inhibiting factor and unforeseen things such as natural disasters such as floods, make it impossible to carry out scheduled Corporate Social Responsibility programs.